Strategi Komunikasi Komisi Pemilihan Umum (KPU) Kabupaten Boyolali Melalui Pendidikan Politik untuk Meningkatkan Partisipasi Pemilih - Raihana Lutfiah Nabila; Sarbini (Syntax Idea)
General Elections (Pemilu) have become one of the essential democratic activities to achieve a more developed Indonesia. As Indonesian citizens, it is paramount to amplify efforts to advocate for their voting rights in democratic processes to use their voters. On the other hand, there are several complexities for voters in the world of democracy. Consequently, as an intermediary between institutions and the community, the Boyolali Regency General Election Commission (KPU) provides insights and information related to political education, further emphasizing activities to foster the spirit of voters during the Elections. The results of this research indicate that active voter participation is increasing with each implementation of the Legislative General Elections. This is based on the concept of "Who Says What In Which Channel To Whom With What Effect?" It has been evidenced that the Boyolali Regency General Election Commission (KPU) has successfully maintained about three times increase in voters exercising their voting rights. While boosting active voter participation, the Boyolali Regency KPU employs communication strategies through political education via socialization and Pancasila Student Profile Strengthening Project (P5) visits to several schools, involving students as first-time voters, community groups, community leaders, and people with disabilities. Communication through mass media platforms such as YouTube, Instagram, and Facebook are also conducted to encourage the audience to continue exercising their voting rights.